Differential subcellular localization of the regulatory T-cell protein LAG-3 and the coreceptor CD4 - Woo, Seng-Ryong (2010)
CD4 binds to MHC class II molecules and enhances T-cell activation. The CD4-related transmembrane protein LAG-3 (lymphocyte activation gene-3, CD223) binds to the same ligand but inhibits T-cell proliferation. We have previously shown that LAG-3 cell surface expression is tightly regulated by extracellular cleavage in order to regulate its potent inhibitory activity. Given this observation and the contrasting functions of CD4 and LAG-3, we investigated the cell distribution, location and transport of these related cell surface molecules. As expected, the vast majority of CD4 is expressed at the cell surface with minimal intracellular localization, as determined by flow cytometry, immunoblotting and confocal microscopy. In contrast, nearly half the cellular content of LAG-3 is retained in intracellular compartments. This significant intracellular storage of LAG-3 appears to facilitate its rapid translocation to the cell surface following T-cell activation, which was much faster for LAG-3 than CD4. Increased vesicular pH inhibited translocation of both CD4 and LAG-3 to the plasma membrane. While some colocalization of the microtubule organizing center, early/recycling endosomes and secretory lysosomes was observed with CD4, significantly greater colocalization was observed with LAG-3. Analysis of CD4:LAG-3 chimeras suggested that multiple domains may contribute to intracellular retention of LAG-3. Thus, in contrast with CD4, the substantial intracellular storage of LAG-3 and its close association with the microtubule organizing center and recycling endosomes may facilitate its rapid translocation to the cell surface during T-cell activation and help to mitigate T-cell activation.